Predictive value of preoperative weight loss on survival of elderly patients undergoing surgery for esophageal squamous cell carcinoma - Zhang, Hanlu; Yang, Yushang; Shang, Qixin; Li, Xiaoyang; Wang, Wenping; Hu, Yang; Yuan, Yong; Wang, Yun; Chen, Long-Qi (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
Background: The role of preoperative weight loss (PWL) has rarely been studied in elderly patients undergoing surgery for esophageal squamous cell carcinoma (ESCC). The aim of this study is to evaluate whether PWL is an important determinant of survival in elderly patients following surgery for ESCC. Methods: This retrospective study included a total of 974 elderly patients (≥65 years) who underwent esophagectomy for ESCC at the West China Hospital, Sichuan University from August 2005 to April 2013. PWL was determined as the percentage weight loss during the 3 months before admission. Patients were divided into three groups according to the PWL, defined as normal (PWL =0), slight PWL (0< PWL